Native : identity, belonging, and rediscovering God - Curtice, Kaitlin B. (Brazos Press, a division of Baker Publishing Group, 2020)
"Native is about identity, soul-searching, and the never-ending journey of finding ourselves and finding God. As both a citizen of the Potawatomi Nation and a Christian, Kaitlin Curtice offers a unique perspective on these topics. In this book, she shows how reconnecting with her Potawatomi identity both informs and challenges her faith. Curtice draws on her personal journey, poetry, imagery, and stories of the Potawatomi people to address themes at the forefront of today's discussions of faith and culture in a positive and constructive way. She encourages us to embrace our own origins and to share and listen to each other's stories so we can build a more inclusive and diverse future. Each of our stories matters for the church to be truly whole. As Curtice shares what it means to experience her faith through the lens of her Indigenous heritage, she reveals that a vibrant spirituality has its origins in identity, belonging, and a sense of place."--